PROFIL KEMAMPUAN KETERAMPILAN BERPIKIR KRITIS ANAK - samudera, Wawan (Al-mujahidah, 2023)
Research on critical thinking skills has been carried out in many countries and found results that critical thinking skills have decreased over time, the decline mainly occurring in kindergarten through third grade. This study aims to determine the profile of children's critical thinking abilities. This research uses a descriptive method. The instrument used in the research is the rubric of critical thinking skills. Data were analyzed using qualitative analysis